META-ANALISIS HUBUNGAN KEPEMIMPINAN KEPALA SEKOLAH DENGAN MOTIVASI KERJA GURU - Indra Rianto; Fivy Aprylianne Andries; Sandra Rakian; Rinny Suryani Rorimpandey; Herry Sumual; Lenny Leorina Evinita (STKIP Pesisir Selatan, 2026)
This study aims to analyze the relationship between principal leadership and teacher work motivation through a meta-analysis approach based on publications from the last five years. The study employed a meta-analysis method by collecting scientific articles from national and international journals relevant to the research topic. Based on the selection process using inclusion criteria, 20 eligible articles were obtained for analysis. Data were analyzed descriptively and comparatively to identify trends in previous research findings. The results showed that principal leadership has a positive relationship with teacher work motivation. A total of 90% of the studies reported significant effects, while the remaining studies indicated moderate positive relationships. Transformational leadership was identified as the most dominant and effective model in improving teacher work motivation, followed by instructional, democratic, and situational leadership. These findings confirm that principals play a strategic role in fostering teachers’ enthusiasm, loyalty, commitment, and productivity. The implications of this study highlight the importance of strengthening principals’ competencies in leadership, communication, academic supervision, and change management as efforts to improve educational quality sustainably.